An efficient scheduling mechanism for IoT-based home automation system. (11th June 2021) - Potluri, Sirisha; Mohanty, Sachi Nandan
Using internet of things (IoT), we can connect and enable every object to send or receive data through the internet. When it comes to real life applications we can make use of this technology for easy communication through home automation. Smart homes, smart agriculture, smart automobiles, and smart electronic gadgets are the examples of IoT-based applications. When more number of objects is connected in distributed environment, controlling and managing the device is much difficult. Due to IoT enabled framework, the number of requests coming to the cloud computing environment is increasing exponentially. The scheduling algorithm which is used in such cases should be efficient to handle various requests coming from these connected devices. The objective of this paper is to develop efficient scheduling mechanism which controls home appliances remotely by using any android or smart phone. Since the devices are connected over cloud computing environment, the proposed method can efficiently schedule the tasks.